KONSENTRASI BOD DAN COD PADA PERAIRAN KURAU, KABUPATEN BANGKA TENGAH - Farah Fiolen; Irma Akhrianti; Mohammad Agung Nugraha (Scientific Timeline, 2023)
Kurau Waters is located in Koba District, Central Bangka Regency which is used for residential activities, fish auction places (TPI), capture fisheries, tourism, and fishing boat docks. This activity has the potential to produce organic waste, whether it has been through a wastewater treatment plant or not. Excess organic matter can cause problems. The purpose of this study was to determine the concentration of BOD and COD in the waters of the Kurau Estuary and to determine the status of BOD and COD pollution based on the relationship between BOD and COD concentrations to the Macrozoobenthos Diversity Index. Laboratory analysis of BOD using titration method and COD using closed reflux method spectrophotometrically. Concentrations of Biochemical Oxygen Demand (BOD) and Chemical Oxygen Demand (COD) in the waters of the Kurau Estuary, Central Bangka Regency have concentration values ranging from 3.10 to 6.80 mg/L and 33.00 – 116.00 mg/L. The status of organic pollution in the waters of the Kurau Estuary is in unpolluted status.